Short-circuit effects on spark ignition engine after-treatment and fuel-to-air ratio control. (June 2020) - Guardiola, Carlos; Pla, Benjamín; Real, Marcelo; Travaillard, Cyril; Dambricourt, Frederic
The short circuit of fresh air is a more and more extended strategy to deal with low-end torque issues, very common in small turbocharged and spark-ignited four-stroke engines. Therefore, from the author's point of view, it is interesting to check whether the after-treatment system can work properly under these conditions. In the present study, the effect of the fresh air short-circuit on engine emissions has been assessed through its impact on the widebandλ sensor and the three-way catalyst behaviour, which are the key elements of the fuel-to-air ratio control strategy. In particular, the analysis of the sensor dynamic response shows that theλ sensor overestimates the fuel-to-air ratio under short-circuit conditions. The sensor overestimation leads the actual fuel-to-air ratio out of the proper three-way catalyst window; in this sense, results show a non-negligible emissions increase, especially in terms of NOx . Regarding the impact on the three-way catalyst behaviour, the study shows how short-circuit pulses change the exhaust gas composition for a given fuel-to-air ratio at catalyst inlet, which also contributes to a penalty in the three-way catalyst efficiency.